2021
DOI: 10.7554/elife.70296
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal sequences during theta rely on behavior-dependent spatial maps

Abstract: Navigation through space involves learning and representing relationships between past, current and future locations. In mammals, this might rely on the hippocampal theta phase code, where in each cycle of the theta oscillation, spatial representations provided by neuronal sequences start behind the animal's true location and then sweep forward. However, the exact relationship between theta phase, represented position and true location remains unclear and even paradoxical. Here, we formalize previous notions o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 80 publications
(157 reference statements)
8
20
0
Order By: Relevance
“…This is because when there is a temporal distance between the agent’s actions and their consequences, the sequential order of past experiences has to be maintained in memory to credit the past states and actions when updating the Q values. The importance of sequentiality is consistent with recent observations that theta sequences in the hippocampus are modulated by the animal’s previous behaviour at the spatial location where the theta sequences occur (Parra-Barrero et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…This is because when there is a temporal distance between the agent’s actions and their consequences, the sequential order of past experiences has to be maintained in memory to credit the past states and actions when updating the Q values. The importance of sequentiality is consistent with recent observations that theta sequences in the hippocampus are modulated by the animal’s previous behaviour at the spatial location where the theta sequences occur (Parra-Barrero et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…Our observation that the compression of distance to theta-phase (time) offset between place-cell pairs remained unaltered during jump trials, despite changes in firing patterns of individual place cells, supports the internally organized hippocampal model. Previous experiments also found that theta time offset of spikes between place-cell pairs remains fixed, despite increasing distances between place-field peaks in larger environments ( 2 ), running speed differences ( 83 ), or different temporal requirements ( 84 ). Yet, action- and environment-anchored reference frames can coexist in the hippocampus ( 85 ).…”
Section: Discussonmentioning
confidence: 90%
“…However, the brain consistently opts for more and smaller fields in certain situations, so this suggests that there are factors beyond the Fisher information that constrain spatial coding in the place cell population. Some variables that might impose additional constraints are the size of obstacles (our simulation did not include any), and temporal coding linked to the behavior of the animal, such as running speed (Parra-Barrero et al, 2021). In addition, there are more generic limitations on efficient coding, i.e.…”
Section: Limits Of Efficient Codingmentioning
confidence: 99%
“…Lee, Griffin, Zilli, Eichenbaum, & Hasselmo, 2006; J.S. Lee, Briguglio, Cohen, Romani, & Lee, 2020; Parra-Barrero, Diba, & Cheng, 2021; Sato et al, 2020; Tryon et al, 2017; Turi et al, 2019; Zaremba et al, 2017). The same observation was made near walls as compared to further away Tanni, De Cothi, and Barry (2022).…”
Section: Introductionmentioning
confidence: 99%